A Biography That Humanizes its Subject: An Analysis of The Biography of Historian Onghokham - Nugraha, Iskandar (Siginjai: Jurnal Sejarah, 2024)
A Biography That Humanizes its Subject: An Analysis of The Biography of Historian Onghokham